2021
DOI: 10.3389/fvets.2021.641022
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Transcriptome Analysis of Live Attenuated Brucella Vaccine Strain S2 on Non-pregnant Cynomolgus Monkeys Without Abortive Effect on Pregnant Cynomolgus Monkeys

Abstract: Brucellosis, caused by Brucella spp., is an important zoonotic disease leading to enormous economic losses in livestock, posing a great threat to public health worldwide. The live attenuated Brucella suis (B. suis) strain S2, a safe and effective vaccine, is widely used in animals in China. However, S2 vaccination in animals may raise debates and concerns in terms of safety to primates, particularly humans. In this study, we used cynomolgus monkey as an animal model to evaluate the safety of the S2 vaccine str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The GO functional enrichment analysis indicated that the most significantly different GO term was signaling pattern recognition receptor activity, while the defense response function contained the largest number of unigenes (64) (Supplementary Figure S6). This result is consistent with the findings of another study, where the defense response function is abundant in monkeys after immunization (79).…”
Section: Identifying Degs Between Horses With and Without Horse Botfl...supporting
confidence: 93%
“…The GO functional enrichment analysis indicated that the most significantly different GO term was signaling pattern recognition receptor activity, while the defense response function contained the largest number of unigenes (64) (Supplementary Figure S6). This result is consistent with the findings of another study, where the defense response function is abundant in monkeys after immunization (79).…”
Section: Identifying Degs Between Horses With and Without Horse Botfl...supporting
confidence: 93%
“…The primary attenuated live vaccines for brucellosis in China include Brucella melitensis strain M5, Brucella suis strain S2, and Brucella abortus strain A19 27 . However, there are many shortcomings, such as persistent infection in vaccinated animals, risk of toxicity reversal, lack of lasting protection, interference with brucellosis diagnosis and so on 28 .Developing a new vaccine needs to verify its effectiveness and safety, which is a time-consuming and expensive process.…”
Section: Discussionmentioning
confidence: 99%
“…However, no safe and effective vaccine has been developed and licensed for human brucellosis so far. China has licensed B. melitensis strain M5, B. suis strain S2, and B. abortus strain A19 as its nationwide approved animal brucellosis vaccines [18], and among them, the S2 vaccine was approved as a multivalent vaccine against the three Brucella species in cattle, small ruminants, and swine, respectively [18,19]. Here, we will discuss the development of the S2 vaccine in China, biological properties of the S2 vaccine as well as its wide use in vaccination programs of China in pursuit of standardization and validation of a harmonized national vaccination campaign in cattle, small ruminants, and swine.…”
Section: Brucellosis In Chinamentioning
confidence: 99%